Ultrasensitive and Signal‐on Electrochemiluminescence Aptasensor Using the Multi‐tris(bipyridine)ruthenium(II)‐β‐cyclodextrin Complexes. Issue 11 (7th November 2014) - Zhao, Yingying; Chen, Hong; Chen, Qiong; Qi, Yantao; Yang, Fan; Tang, Jie; He, Pingang; Zhang, Fan
Abstract An ultrasensitive and signal‐on electrochemiluminescence (ECL) aptasensor to detect target protein (thrombin or lysozyme) was developed using the host‐guest recognition between a metallocyclodextrin complex and single‐stranded DNA (ss‐DNA). The aptasensor uses both the photoactive properties of the metallocyclodextrins named multi‐tris(bipyridine)ruthenium(II)‐β‐cyclodextrin complexes and their specific recognition with ss‐DNA, which amplified the ECL signal without luminophore labeling. After investigating the ECL performance of different multi‐tris(bipyridine)ruthenium(II)‐β‐cyclodextrin (multi‐Ru‐β‐CD) complexes, tris‐tris(bipyridine)‐ruthenium(II)‐β‐cyclodextrin (tris(bpyRu)‐β‐CD) was selected as a suitable host molecule to construct an atasensor. First, double‐stranded DNA (ds‐DNA) formed by hybridization of the aptamer and its target DNA was attached to a glassy carbon electrode via coupling interaction, which showed low ECL intensity with 2‐(dibutylamino) ethanol (DBAE) as coreactant, because of the weak recognition between ds‐DNA and tris(bpyRu)‐β‐CD. Upon addition of the corresponding protein, the ECL intensity increased when target ss‐DNA was released because of the higher stability of the aptamer‐protein complex than the aptamer‐DNA one. A linear relationship was observed in the range of 0.01 pmol/L to 100 pmol/L between ECL intensity and the logarithm of thrombin concentrations with a limited detection of 8.5 fmol/L (S/N=3). Meanwhile, the measured concentration of lysozyme was from 0.05 pmol/L to 500 pmol/L and the detection limit was 33 fmol/L (S/N=3). The investigations of proteins in human serum samples were also performed to demonstrate the validity of detection in real clinical samples. The simplicity, high sensitivity and specificity of this aptasensor show great promise for practical applications in protein monitoring and disease diagnosis.